Characteristics Associated With Being Asked About Violence Victimization in Health Care: A Swedish Random Population Study - Simmons, Johanna (Journal of interpersonal violence, 2022)
Recommendations to routinely question patients about violence victimization have been around for many years; nonetheless, many patients suffering in the aftermath of violence go unnoticed in health care. The main aim of this study was to explore characteristics associated with being asked about experiences of violence in health care and thereby making visible victims that go unnoticed. In this study, we used cross-sectional survey data from 754 men (response rate 35%) and 749 women (response rate 38%) collected at random from the Swedish population, age 25?85. Questions were asked about experiences of emotional, physical, and sexual violence from both family, partner, and other perpetrators. Only 13.1% of those reporting some form of victimization reported ever being asked about experiences of violence in health care. Low subjective social status was associated with being asked questions (adj OR 2.23) but not with victimization, possibly indicating prejudice believes among providers concerning who can be a victim of violence. Other factors associated with increased odds of being asked questions were: being a woman (adj OR 2.09), young age (24?44 years, adj OR 6.90), having been treated for depression (adj OR 2.45) or depression and anxiety (adj OR 2.19) as well as reporting physical violence (adj OR 2.74) or polyvictimization (adj OR 2.85). The main finding of the study was that only few victims had been asked questions. For example, among those reporting ≥4 visits to a primary care physician during the past 12 months, 43% reported some form of victimization but only 6% had been asked questions. Our findings underline the importance of continuing to improve the health care response offered to victims of violence.